2019
DOI: 10.1093/beheco/arz055
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific pace-of-life syndromes

Abstract: The pace-of-life syndrome (POLS) hypothesis considers an animal’s behavior, physiology, and life history as nonindependent components of a single integrated phenotype. However, frequent deviations from the expected correlations between POLS traits suggest that these relationships may be context, and potentially, sex dependent. To determine whether the sexes express distinct POLS trait covariance structures, we observed the behavior (mobility, latency to emerge from a shelter), physiology (mass-specific metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…We used an experimental setup for the behavioural assays that has been utilised in previous studies (Moschilla et al, 2019(Moschilla et al, , 2020a. A 31 cm deep plastic trough (32 × 46 cm at base) was used as the trial arena.…”
Section: Behavioural Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an experimental setup for the behavioural assays that has been utilised in previous studies (Moschilla et al, 2019(Moschilla et al, , 2020a. A 31 cm deep plastic trough (32 × 46 cm at base) was used as the trial arena.…”
Section: Behavioural Trialsmentioning
confidence: 99%
“…I G U R E 1 Diagram of the arena used for behavioural trials including the position of the speaker used to broadcast male song (fromMoschilla et al, 2019) …”
mentioning
confidence: 99%
“…Although some studies have previously shown sex-specific relationships between AMR and behaviours ( e.g. , Niitepõld et al, 2011 ; Moschilla, Tomkins & Simmons, 2019 ; Methling et al, 2020 ), these behaviours were not tested repeatedly. Thus, to our knowledge, ours is the first to investigate the relationship between AMR and repeatable behaviour or personality traits on a sex-specific basis.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted an experimental design for the behavioural trials that has been used in previous studies [41][42][43][44] figure S1). Each behavioural trial began by placing an individual cricket into the shelter within the arena, with the door closed (electronic supplementary material, figure S1).…”
Section: (D) Mate Searching Behavioural Trialsmentioning
confidence: 99%